The Proapoptotic Protein tBid Forms Both Superficially Bound and Membrane-Inserted Oligomers - Shivakumar, Sanjeevan (The Biophysical Society, 2014)
Bid is a proapopotic activator protein of the Bcl-2 family that plays a pivotal role in controlling mitochondrial outer membrane permeabilization during apoptosis. Here, we characterized the interaction of fluorescently labeled truncated Bid (tBid) with a mitochondria-like supported lipid bilayer at the single-molecule level. The proteins observed at the membrane exhibited a very wide range of mobility. Confocal images of the membrane displayed both diffraction-limited Gaussian spots and horizontal streaks, corresponding to immobile and mobile tBid species, respectively. We observed 1), fast-diffusing proteins corresponding to a loosely, probably electrostatically bound state; 2), slowly diffusing proteins, likely corresponding to a superficially inserted state; and 3), fully immobilized proteins, suggesting a fully inserted state. The stoichiometry of these proteins was determined by normalizing their fluorescence intensity by the brightness of a tBid monomer, measured separately using fluorescence fluctuation techniques. Strikingly, the immobile species were found to be mainly tetramers and higher, whereas the mobile species had on average a significantly lower stoichiometry. Taken together, these results show that as soluble Bid progresses toward a membrane-inserted state, it undergoes an oligomerization process similar to that observed for Bax.